Bentuk Perilaku Kekerasan dan Diskriminasi Terhadap Tokoh Dalam Novel 00.00 Karya Ameylia Falensia: Kajian Teori Johan Galtung - Rahmawati, Astri; Effendi, Darwin; Wandiyo, Wandiyo (Indonesian Research Journal on Education, 2022)
This purpose of this study to determine the form of violent behavior and discrimination againstcharacters in the novel 00.00 by Ameylia Falensia using Johan Galtung's theory of violence anddiscrimination in schools. The research method used is a qualitative descriptive method. In thisstudy, data collection used literature study techniques, namely reading techniques and note-taking techniques. The results showed the following results. This research resulted in an analysis of violence and discrimination in the novel 00.00 by Ameylia Falensia, the analysis of violence produced two forms of violence, namely (1) direct violence, and (2) structural violence. Direct violence is divided into direct physical violence and direct violence verbally. The violence was immediately received by the Lengkara and Masnaka figures in the form of beatings, sightings, and harsh words. And the sturktural violence was accepted by the figures of Nina, Aslan, Masnaka, Prima, and Deo. Research on discrimination focuses on discrimination in schools, namely the occurrence of bullying/bullying received by the main actors.